2018
DOI: 10.1016/j.smallrumres.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of milk production losses and variations of fat and protein percentages according to different levels of somatic cell count in Valle del Belice dairy sheep

Abstract: The somatic cell count (SCC) of milk is widely used to monitor udder health and the milk quality and because of its positive genetic correlation with mastitis this trait was included in breeding schemes of dairy sheep. The aim of this study was to estimate the loss in milk yield (MY) and related composition resulting from different levels of somatic cell count in Valle del Belice dairy sheep. Data were collected between 2006 and 2016 in 15 flocks following an A4 recording scheme. Somatic cell count (SCC), fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
1
7
1
3
Order By: Relevance
“…The peak of production is related to the lactose content for Santa Ines ewes, reported the major level of production at 37 DIM 7 . This is correlated with found here for lactose content which was higher in group two (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); also, the results of this study are similar to reported by others 29 , who correlated the percentage of lactose and production peak, and found that this occurred in the third week (21 DIM) for Talaverana breed.…”
Section: Discussionsupporting
confidence: 92%
“…The peak of production is related to the lactose content for Santa Ines ewes, reported the major level of production at 37 DIM 7 . This is correlated with found here for lactose content which was higher in group two (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); also, the results of this study are similar to reported by others 29 , who correlated the percentage of lactose and production peak, and found that this occurred in the third week (21 DIM) for Talaverana breed.…”
Section: Discussionsupporting
confidence: 92%
“… Kelly et al (2000) found that an elevated SCC can alter the protein fractions distribution; decrease casein and lactose levels in milk; increase rennet clotting time, cheese moisture, and losses of fat and proteins in whey, and reduce curd firmness and cheese yielding. A study conducted by Sutera et al (2018) confirmed that high levels of SCC in sheep milk are associated with milk yield losses and variations of fat and protein percentages. The estimated losses in milk yield ranged from 883 g for SCC ≤ 2,000 × 10 3 to 1,052 g for SCC ≤ 500 × 10 3 with an overall decrease of 16%, whereas fat and protein percentages increased to 0.06 and 0.29%, respectively.…”
Section: Introductionmentioning
confidence: 89%
“…In a sheep flock with 75% infected glands, a decrease in production of 12.2% was observed [1], whereas in goats, with the same percentage of infected glands, the losses were 2.3%. A production loss related to the increase in SCC was also reported [2], reaching 16% when the threshold of 500 × 103 cells/mL was exceeded, emphasising the importance of implementing SCC control programmes in sheep. Mastitis also causes an alteration in milk composition and a consequent decrease in cheese yield, more pronounced in sheep than in cattle or goats [3].…”
Section: Introductionmentioning
confidence: 92%